PENGAWASAN BERPENGARUH TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT KECAMATAN PLAKAT TINGGI - Fery Suprianto (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2017)
The purpose of this study is to see the Effect of Supervision toward EmployeePerformance at sub-district Office of Plakat Tinggi Musi Banyuasin Regency. Thetheoretical basis that the author used were Definition of Management, Definition ofHuman Resource Management, Definition of Supervision, Monitoring Indicators,Supervision Objectives, Types of Supervision, Engineering Supervision, PerformanceDefinition, Performance Indicators, Performance Affecting Factors, PerformanceAssessment, Objectives and Benefits of Assessment Performance, and PerformanceAppraisal Criteria. Dependent variable used in this research was Employee Performanceand independent variable was supervision. Populations and samples in this study were30 employees. The author used data collection techniques by using questionnaires,documentation and observation. Data analysis techniques used simple linear regressionanalysis. This study found that Supervision had a positive and significant influencetoward Employees Performance at the Sub-district office of Plakat Tinggi.